Giant juvenile fibroadenoma: a case report - Pareek, Prashant; Pareek, Priyanka (International Surgery Journal, 2018)
Breast Lumps are not a common occurrence in paediatric patients. When encountered, they call for a thorough workup and meticulous treatment plan. Like in adults, fibroadenomas can be seen in children. These are termed ’juvenile fibroadenomas’. When these are larger than 5cm or weigh more than 500gm, they can be called ’giant juvenile fibroadenomas’. These comprise 1-8% of breast lumps in adolescent population. We report here a case of a 10 years old girl who presented with a rapidly growing unilateral breast lump which provided a diagnostic dielemma but was diagnosed as giant juvenile fibroadenoma on histopathology performed post excision. She was successfully treated surgically by removing the entire well-defined lump intact after raising overlying breast flaps. The post-operative period was uneventful. The patient shows no signs of recurrence or co-morbidity even now at follow up OPD visits.